News and Views on TESOL at the Start of the 21" Century - Barbara Mullock (TEFLIN Journal: A publication on the teaching and learning of English, 2002)
Abstract: Teachers of English as a Foreign Language can often feel out of touch with developments in TESOL in native English speaking countries. Information about developments may arrive in sporadically, in discontinuous spurts, and they may not be sure about the accuracy of the picture they are getting, or about how they should be teaching. This paper is a personal attempt to trace important developments and issues in TESOL over the last 25 years, and to suggest ways in which these can affect the performance of the classroom EFL teacher. A number of important recent developments and issues discussed here, including the analysis of language (particularly in ESP) and the teaching of grammar, task-based learning, second language acquisition, and Critical Pedagogy.